NEW FORM OF SEPARATION AXIOMS IN FUZZY SOFT SEQUENTIAL TOPOLOGICAL SPACES - K. Japhia Tino Mercy; K. Bageerathi (Utilitas Mathematica, 2025)
The objective of this paper is to explore separation axioms in fuzzy soft sequential topological spaces. In 2002, Bose and Indrajit Lahiri [2] gave the concept of separation axioms in sequential topological spaces. In 2018, Mahanta and Das [7] introduced fuzzy soft point and studied separation axioms in fuzzy soft topological spaces. Khedr et al [6] introduced fuzzy soft separation axioms in terms of the modified definitions of the fuzzy soft point and study some of the properties in the year 2019. By the way of above concepts, we introduce the separation axioms in a new way in fuzzy soft sequential topology. We define fuzzy soft sequential axioms ( ) using the concept of fuzzy soft sequential quasi-coincident relation between fuzzy soft sequential set and fuzzy soft sequential point and discuss some properties of these spaces with proper examples in detail.